The impact of a training program for the development of types of electricity in kindergarten children (Journal of the College of Basic Education, 2025)
1-The current study aims to investigate the effect.1 of a training program on developing electrical concepts among kindergarten children. The :following hypotheses are included2-There are no statistically significant differences .2 between the mean rank scores of children in the experimental group on the electrical concepts test before and after applying the training program at a significance level of .0.053-There are no statistically significant differences .3 between the rank scores of children in the control group on the electrical concepts test in the pretest and posttest at a significance level .of 0.054- There are no statistically significant differences .4 between the mean rank scores of children in the experimental and control groups on the electrical concepts test in the posttest at a .significance level of 0.05The study population included children from government kindergartens affiliated with the six directorates of education in the Baghdad governorate, covering both Al-Karkh and Al- Rusafa sides. To achieve the objective of the study, the researcher adopted the integrative theory in writing the electrical concepts test, which consisted of 24 items. Two alternative forms were defined, namely (0, 1). After administering the test individually to a sample of 300 children, aged between 5-6, it was statistically analyzed. Additionally, the researcher developed a program to develop electrical concepts, consisting of 10 sessions, which was applied to a sample of 30 children divided into experimental and control groups, 15 children each. The researcher ensured that the experimental and control groups are matched in certain variables that could influence the results, based on the theoretical frameworks and previous literature, as well as the pretest. The researcher verified the psychometric properties of the tool used in the study, including validity and reliability. The face validity and construct validity were ensured, while the reliability of the electrical concepts test was calculated using the Kuder-Richardson 20 formula. The study results:showed that